AI-Driven generative prototyping for the reconstruction of Gaza - Graziella Bernardo; Luis Palmero Iglesias (Vitruvio: International Journal of Architectural Technology and Sustainability, 2025)
Rafael Leoz (1921–1976), Spanish architect and theorist, made a pioneering yet underacknowledged contribution to modular and participatory architecture through his HELE module (Habitación Expandible Lineal Evolutiva), a combinatorial system based on polyhedral logic and open-ended design. Originally conceived as a response to post-war housing shortages in Spain, the HELE system promoted structural flexibility, user autonomy, and community participation. Despite receiving praise from figures like Le Corbusier and a nomination for the Nobel Peace Prize in 1968, Leoz’s work remains marginal in architectural historiography. This article repositions his legacy within the framework of contemporary humanitarian and environmental challenges. Through critical study of technical and scientific literature and AI-driven design, we reinterpret the HELE module as a framework for ethical and context-sensitive architecture. The paper proposes a speculative reconstruction model for Gaza that integrates AI-driven parametric design, sustainable materials such as compressed earth blocks and recycled rubble, and participatory construction practices. The outcomes underscore the potential of systemic, modular design to support resilience, collective agency, and spatial justice in post-conflict territories. The study demonstrates how AI can function not as a substitute for human creativity but as an ally in realizing adaptive, inclusive, and materially grounded architectural futures, extending Leoz’s vision into the 21st century.